Potential modeling of pavement deterioration rate due to cracking - Wee, S.Y; Chan, R.A.@R.B.; Razali, I. (Universiti Malaysia Sarawak (UNIMAS), 2009)
Bitumen pavements tend to crack at some point of their life under the combined action of traffic and the environment. These cracks are defects in the pavement surfacing which weakens the pavement and allows water to penetrate and cause further weakening. Once initiated, cracking usually increases in extent, severity and intensity, leading eventually to pavement failure. Cracking has therefore been an important indicator for road pavement maintenance.